(untitled) (LEGAL DIALOGICA, 2025)
Objective The research is to find out and analyse how the procedures as well as the procedures and mechanism for registration of trademark rights according to Law No. 20 of 2016 on Trademarks and Geographical Indications. 2016 on trademarks and geographical indications. This research is a normative research normative research conducted to find the actual truth. Source of legal materials The source of legal material used is the approach of legislation, legal theory legal theory, and rules that are in accordance with the dispute resolution of the sale and purchase of goods through social media. buying and selling goods through social media. Methods This research uses the method of normative research method. And the results of this study Trademark registration has has a fairly strict regulation starting from the application for registration of a trademark until the issuance of a trademark certificate. a trademark until the issuance of a certificate of Trademark Rights. However, there are still However, there are still problems such as bad applicants (bad faith) and trademark application examiner operators who still pass the trademark that has similarities with other trademarks. that have similarities with other trademarks, giving rise to disputes over trademarks in the future. Trademark in the future. Recommendations in This research, additional regulations are needed that are more stringent so that the operator examiners in authorising applications for registration of trademarks do not incorrectly authorise a trademark that has a similarity of name. The need for regulation or platform that is easier and more efficient for the community to register their trademarks. Abstrak: Tujuan Penelitian untuk untuk mengetahui dan menganalisis bagaimana tata cara serta prosedur mekanisme pendaftaran hak merek menurut Undang-Undang Nomor 20 Tahun 2016 tentang merek dan Indikasi geografis. Penelitian ini adalah penelitian normatif dilakukan untuk menemukan kebenaran yang sebenarnya. Sumber bahan hukum yang digunakan ialah pendekatan peraturan perundang-undangan, teori hukum, dan aturan aturan yang sesuai dengan penyelesai sengketa terhadap jual beli barang melalui media sosial.. Metode penelitian ini menggunakan metode penelitian normatif. Dan hasil dari penelitian ini Pendaftaran merek telah memiliki regulasi yang cukup ketat dimulai dari permohonan pendaftaran atas suatu merek sampai dikeluarkannya sertifikat Hak atas Merek. Akan tetapi masih terdapat persoalan seperti pemohon dengan bad applicant (beritikad tidak baik) dan operator pemeriksa permohonan pendaftaran merek yang masih meloloskan merek yang memiliki kesamaan dengan merek lain, sehingga menimbulkan sengketa atas Merek dikemudian hari. Rekomendasi dalam penelitian ini, Diperlukan regulasi tambahan yang lebih ketat agar operator pemeriksa dalam mengesahkan permohonan pendaftaran merek tidak salah mengesahkan merek yang memiliki kemiripan nama. Perlunya regulasi atau platfrom yang lebih mudah dan efisian untuk masyarakt mendaftarkan mereknya.